2015
DOI: 10.12659/aot.892966
|View full text |Cite
|
Sign up to set email alerts
|

Antithymocyte Globulin Dosing Effects on Biopsy-Proven Acute Rejection and Infection Risk

Abstract: Five doses of rATG versus 3 doses did not provide any additional benefit in preventing BPAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Previous studies demonstrated that allograft rejection in different induction regimens appears to be similar, but higher doses of ATG are thought to be associated with an increased risk of death and infection [1418]. Our study showed higher rejection episodes in the non-induction group compared to the other groups, but this difference was not statistically significant, and the dosage of ATG did not affect allograft survival.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies demonstrated that allograft rejection in different induction regimens appears to be similar, but higher doses of ATG are thought to be associated with an increased risk of death and infection [1418]. Our study showed higher rejection episodes in the non-induction group compared to the other groups, but this difference was not statistically significant, and the dosage of ATG did not affect allograft survival.…”
Section: Discussioncontrasting
confidence: 64%